The Strategy of Content Marketing to Increase The Revenue of Fundamental Hypnosis Training at Course Institute and Indonesian Hypnosis Centre Training in Mataram City - Arrosi, Muhlis; Pasaribu, Fajar; Indahwati, Rini (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
This research aims to identify and analyze the content marketing strategies employed by the Indonesian Hypnosis Centre (IHC) to enhance revenue from the Fundamental Hypnosis training in Mataram City, West Nusa Tenggara Province. The primary issue under investigation is revenue instability, with a focus on utilizing unpaid content marketing strategies on Instagram as an alternative solution. Through a qualitative approach involving in-depth interviews and secondary data analysis, this study reveals that before 2018, IHC relied solely on paid marketing methods such as purchasing provider numbers and distributing brochures. However, since its introduction in 2018, Instagram content marketing has proven effective starting in 2019. A consistent, though modest, increase in participant contributions from Instagram has been observed. Additionally, the research explores the use of editing tools such as CapCut, CorelDRAW, and Filmora, and the benefits of microblogging and Instagram Reels within the content marketing strategy. The findings are expected to provide significant contributions to the development of content marketing strategies for training institutions, particularly in the field of hypnosis, to address the challenge of unstable revenue